The Scottish Early Rheumatoid Arthritis (SERA) Study: an inception cohort and biobank. Issue 1 (December 2016) - Dale, James; Paterson, Caron; Tierney, Ann; Ralston, Stuart; Reid, David; Basu, Neil; Harvie, John; McKay, Neil; Saunders, Sarah; Wilson, Hilary; Munro, Robin; Richmond, Ruth; et al.
Abstract Background The Scottish Early Rheumatoid Arthritis (SERA) study is an inception cohort of rheumatoid (RA) and undifferentiated arthritis (UA) patients that aims to provide a contemporary description of phenotype and outcome and facilitate discovery of phenotypic and prognostic biomarkers Methods Demographic and clinical outcome data are collected from newly diagnosed RA/UA patients every 6 months from around Scotland. Health service utilization data is acquired from Information Services Division, NHS National Services Scotland. Plain radiographs of hands and feet are collected at baseline and 12 months. Additional samples of whole blood, plasma, serum and filtered urine are collected at baseline, 6 and 12 months Results Results are available for 1073 patients; at baseline, 76 % were classified as RA and 24 % as UA. Median time from onset to first review was 163 days (IQR97-323). Methotrexate was first-line DMARD for 75 % patients. Disease activity, functional ability and health-related quality of life improved significantly between baseline and 24 months, however the proportion in any employment fell (51 to 38 %, p = 0.0005). 24 % patients reported symptoms of anxiety and/or depression at baseline. 35/391 (9 %) patients exhibited rapid radiographic progression after 12 months. The SERA Biobank has accrued 60, 612 samples Conclusions In routine care, newly diagnosed RA/UA patients experience significant improvements in disease activity, functional ability and health-related quality of life but have high rates of psychiatric symptoms and declining employment rates. The co-existence of a multi-domain description of phenotype and a comprehensive biobank will facilitate multi-platform translational research to identify predictive markers of phenotype and prognosis